2000
DOI: 10.1159/000028930
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Acute Giant Epidural Hematoma in a Hydrocephalic Shunted Child

Abstract: Extradural hematoma (EDH) is considered to be a rare complication of head trauma in children, and represents a serious and urgent pathology from which complete recovery can be expected if specialized treatment is instituted in time. In this article, the authors report the potential danger to a hydrocephalic shunted child who was apparently asymptomatic at the time of hospital admission with a mild head injury and developed an EDH of venous origin. This child had a rapid (time interval from injury to decerebrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
(33 reference statements)
0
3
0
1
Order By: Relevance
“…This consists mostly of case reports and small series, which postulated an increased risk of intracranial injury due to stretching of bridging vessels, 16 or potential delayed detection due to transient overcompensatory CSF drainage or VS fracture. 7,17 Patients with a VS have an increased radiation burden compared with the general population due to more frequent use of CT scans to investigate potential shunt malfunction, with consequent increased risk of developing radiation-associated malignancies. 10,11 Strategies to reduce this burden have been proposed in the form of limited-sequence CT scanning, 18 or fast MRI protocols, although these may not be practical in the context of TBI due to view limitations and the potential incompatibility of shunts with MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This consists mostly of case reports and small series, which postulated an increased risk of intracranial injury due to stretching of bridging vessels, 16 or potential delayed detection due to transient overcompensatory CSF drainage or VS fracture. 7,17 Patients with a VS have an increased radiation burden compared with the general population due to more frequent use of CT scans to investigate potential shunt malfunction, with consequent increased risk of developing radiation-associated malignancies. 10,11 Strategies to reduce this burden have been proposed in the form of limited-sequence CT scanning, 18 or fast MRI protocols, although these may not be practical in the context of TBI due to view limitations and the potential incompatibility of shunts with MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Some therefore have suggested that all children with a VS should undergo CT scanning after any TBI, regardless of their clinical presentation. 7,8 In the largest series to date from the PECARN group, the prevalence of clinically important TBI (ciTBI) and injuries seen on CT scanning were no higher than that in the population without a VS. 9 Despite this, CT usage rates were higher in children with VS than in the general population. Safe reduction in the use of CT is required, as repeated radiological evaluations for potential VS failure result in a higher cumulative lifetime radiation dose, increasing the risk of radiation-associated neoplasms in these children.…”
mentioning
confidence: 96%
“…O sistema de DVP concorre para a ausência de sintomas e sinais clínicos e neurológicos associados à presença de coleções hemorrágicas, visto que o shunt funcionante resulta em drenagem contínua de LCR e rápido acúmulo de sangue, sem aumento significativo da pressão intracraniana, podendo explicar, assim, a evolução crônica dessa complicação com o achado de grandes coleções com pouca ou nenhuma sintomatologia e a piora abrupta do quadro neurológico 9 .…”
Section: Discussionunclassified
“…The patient is dependent on the VPS, yet its presence risks the loss of the tamponading effect of CSF, allowing the hematoma to rapidly grow unabated [15]. This offers an attractive argument for the use of programmable shunts, offering the option of a slow, gradual lowering of CSF pressure and, should hemorrhage occur, pressure may be manipulated as needed.…”
Section: Discussionmentioning
confidence: 99%